2013
DOI: 10.1186/1471-2369-14-207
|View full text |Cite
|
Sign up to set email alerts
|

BK viremia and polyomavirus nephropathy in 352 kidney transplants; risk factors and potential role of mTOR inhibition

Abstract: BackgroundPolyomavirus BK nephropathy (PyVAN) remains an important cause of early graft dysfunction and graft loss in kidney transplantation.MethodsIn this retrospective, single centre cohort study we studied the incidence and outcome of BK viral infection in 352 patients transplanted in 2008–2011.ResultsDuring follow-up viral replication was detected in 48 patients (13.6%); 22 patients (6.2%) had biopsy proven PyVAN.In multivariate logistic regression analyses risk factors for BK-viremia were lack of enrolmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 38 publications
(37 reference statements)
3
56
1
Order By: Relevance
“…In patients with negative screening for BKPyV, the authors observed an improved renal allograft function within the first year after transplantation compared to patients with BKPyV viremia and/or PyVAN. However, the patients with BKPyV viremia were not subdivided into groups based on quantified BKPyV viral load in serum . In the current study, patients with BKPyV viremia were subdivided according to their maximal detected BKPyV load in serum until 24 months after transplantation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In patients with negative screening for BKPyV, the authors observed an improved renal allograft function within the first year after transplantation compared to patients with BKPyV viremia and/or PyVAN. However, the patients with BKPyV viremia were not subdivided into groups based on quantified BKPyV viral load in serum . In the current study, patients with BKPyV viremia were subdivided according to their maximal detected BKPyV load in serum until 24 months after transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of serum BKPyV viremia ≤10 4 copies/mL was not previously evaluated in the literature. A retrospective study by Jacobi et al observed an impact of the BKPyV viremia on the graft function. In patients with negative screening for BKPyV, the authors observed an improved renal allograft function within the first year after transplantation compared to patients with BKPyV viremia and/or PyVAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they are associated with lesser CMV viremia [69], and everolimus was shown to be superior to MMF in that aspect in a pooled analysis of three clinical trials [70]. Additionally, mTOR-I showed favourable effect in BK viremia/BK associated nephropathy [71,72] and post-transplant encapsulating peritoneal sclerosis [73][74][75].…”
Section: Introduction and Overview Of Immunosuppressant In Kidney Tramentioning
confidence: 99%
“…The issue has become more important in recent years, as several new immunosuppressant agents have been introduced for treating renal transplant recipients. PVAN is an aggressively destructive disease occurring in up to 8% of kidney allograft recipients [3], with one-year graft-loss rate ranging from 30% to 65% [4]. PVAN has become an important cause of allograft loss in renal transplantation, but only limited information is available regarding its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%